DAMPAK LAYANAN DAN KUALITAS SISTEM PADA KEPUASAN PELANGGAN - Herman Sjahruddin; Ketut Asteri (JEMBATAN, 2021)
Customer satisfaction is an important factor in the sustainability of the company. Some researchers explore the determining factors of creating customer satisfaction. Based on the statement, this study retests the effect of service quality and system quality on customer satisfaction. The data obtained in this study was obtained through the dissemination of questionnaires with a sample number of 120 respondents and there were 21 data that were not used because they did not meet the criteria in the study. Sampling techniques in this study is accidental sampling, the results of regression testing show that good quality of service will drive the level of customer satisfaction. The condition is different from the quality of the system which shows that the quality of the system does not contribute to customer satisfaction